2020
DOI: 10.1080/21582041.2020.1733646
|View full text |Cite
|
Sign up to set email alerts
|

Examining employees’ behavioural outcomes within the context of organisational justice

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
5
3
0
Order By: Relevance
“…Participants who perceived their organisation's systems to be ethical, consistent, precise and devoid of potential discrimination seemed to perceive a higher level of overall employee commitment, show psychological attachment and express sentiments to stay or extend their stay with the employing organisation. These findings are consistent with those of Waribo et al (2020), who reported that employees' perceptions of the fairness processes in the organisation related positively with their perceptions of employee commitment. In a similar study, Turgut, Tokmak and Gucel (2012) stated that fairness plays an important role in employee evaluation of the workplace environment.…”
Section: Relationship Between Organisational Justice and Employee Com...supporting
confidence: 91%
“…Participants who perceived their organisation's systems to be ethical, consistent, precise and devoid of potential discrimination seemed to perceive a higher level of overall employee commitment, show psychological attachment and express sentiments to stay or extend their stay with the employing organisation. These findings are consistent with those of Waribo et al (2020), who reported that employees' perceptions of the fairness processes in the organisation related positively with their perceptions of employee commitment. In a similar study, Turgut, Tokmak and Gucel (2012) stated that fairness plays an important role in employee evaluation of the workplace environment.…”
Section: Relationship Between Organisational Justice and Employee Com...supporting
confidence: 91%
“…This PSR, in turn, is associated with the purchase intentions of followers. In contrast, the earlier study byYuan and Lou (2020) suggested that only distributive and informational fairness indirectly influence the product interest via PSR.The findings of this study are also in line with the findings of earlier studies conducted byWaribo et al (2020) that all four dimensions of fairness significantly positively influence employee behaviour outcomes via employee perception. Moreover, the study conducted byHan et al (2019) suggested that distributive, procedural, and interpersonal fairness significantly positively influence customer satisfaction via customer psychological empowerment.…”
supporting
confidence: 90%
“…Continuing with this theme, Waribo et al (2020) highlights the positive influence of organisational justice on employee satisfaction, commitment and engagement in the Nigerian public sector. The authors link the six dimensions of organisational justicedistributive, procedural, interpersonal, informational, spatial and temporalto employees' perceptions of fairness in the organisation.…”
Section: Employee Reactions To Changementioning
confidence: 84%